Crustal structure beneath the Rif Cordillera, North Morocco, from the RIFSIS wide‐angle reflection seismic experiment. (9th December 2014) - Gil, Alba; Gallart, Josep; Diaz, Jordi; Carbonell, Ramon; Torne, Montserrat; Levander, Alan; Harnafi, Mimoun
Abstract The different geodynamic models proposed since the late 1990s to account for the complex evolution of the Gibraltar Arc System lack definite constraints on the crustal structure of the Rif orogen. Here we present the first well‐resolved P‐wave velocity crustal models of the Rif Cordillera and its southern continuation toward the Atlas made using controlled‐source seismic data. Two 300+ km‐long wide‐angle reflection profiles crossed the Rif along NS and EW trends. The profiles recorded simultaneously five land explosions of 1Tn each using ∼850 high frequency seismometers. The crustal structure revealed from 2‐D forward modeling delineates a complex, laterally varying crustal structure below the Rif domains. The most surprising feature, seen on both profiles, is a ∼50 km deep crustal root localized beneath the External Rif. To the east, the crust thins rapidly by 20 km across the Nekkor fault, indicating that the fault is a crustal scale feature. On the NS profile the crust thins more gradually to 40 km thickness beneath Middle Atlas and 42 km beneath the Betics. These new seismic results are in overall agreement with regional trends of Bouguer gravity and are consistent with recent receiver function estimates of crustal thickness. The complex crustal structure of the Rif orogen in the Gibraltar Arc is a consequence of the Miocene collision between the Iberian and African plates. Both the abrupt change in crustal thickness at the Nekkor fault and the unexpectedly deep Rif crustal root can be attributed to interaction of the subducting Alboran slab with the North African passive margin at late Oligocene‐early Miocene times.